Radiomics-guided deep neural networks stratify lung adenocarcinoma prognosis from CT scans - Hwan-ho Cho (Nature Portfolio, 2021)
Cho et al. use a radiomics-guided deep-learning approach to model the prognosis of lung adenocarcinoma from CT scan data. This study demonstrates the utility of this technology as a predictive approach for stratifying clinical prognostic groups.